2001
DOI: 10.1099/0022-1317-82-4-845
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of B cells and IFN-γ-secreting CD4+ T cells in innate and adaptive immune control of genital herpes simplex virus type 2 infection in mice

Abstract: The role of B, CD4 M T and CD8 M T cells in both primary genital infection with attenuated herpes simplex virus type 2 (HSV-2) and development of protective immunity to a later challenge with virulent HSV-2 using lymphocyte-deficient mice has been elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 41 publications
11
118
0
Order By: Relevance
“…However, IFN-␥ responses in the lymphoid organs appeared to be dominant. We and others have previously documented the critical importance of IFN-␥ response for immune protection against genital herpes infection in mice (23)(24)(25)(26). Furthermore, we could show that mice immunized with gD plus ␣-GalCer had high levels of gD-specific IgG Abs in their sera and vaginal extracts.…”
Section: Discussionsupporting
confidence: 54%
“…However, IFN-␥ responses in the lymphoid organs appeared to be dominant. We and others have previously documented the critical importance of IFN-␥ response for immune protection against genital herpes infection in mice (23)(24)(25)(26). Furthermore, we could show that mice immunized with gD plus ␣-GalCer had high levels of gD-specific IgG Abs in their sera and vaginal extracts.…”
Section: Discussionsupporting
confidence: 54%
“…In the absence of T-bet, CD8+ T cells may produce higher amounts of the cytokine, since T-bet is not able to inhibit IL-2 production, which may, at least to some extent, be the case in wild-type cells. Moreover, the role of CD8+ T cells may be of minor importance during HSV-2 infection, since mice depleted of CD8+ T cells are still able to clear the infection after vaccination (Harandi et al, 2001), which may also explain the loss of function of T-bet in HSV-2-specific CD8+ T cells. In contrast to HSV-2 infection, T-bet is necessary for the antigen-driven development of CD8+ T cells into effector cells, and for a sufficient cytotoxic response together with optimal IFN-γ production in response to lymphocytic choriomeningitis virus (Sullivan et al, 2003).…”
Section: Cd8+ T Cellsmentioning
confidence: 99%
“…Hence, antibody-mediated immunity is insufficient for protection against, e.g., Chlamydia trachomatis or herpes simplex virus 2 infections [1][2][3]. Rather, these infections can only be prevented by robust Ag-specific CD4 1 T cells in the genital tract, as documented in several of the animal models of these infections [2,4,5]. Previous studies have shown that i.n.…”
Section: Introductionmentioning
confidence: 99%